From Selective to Non-Selective Vibrational Predissociation in Glyoxal van der Waals Complexes. Issue 3 (1983) - Halberstadt, N.; Soep, B.
Abstract : Vibrational predissociation (VP) of glyoxal complexes formed in a supersonic expansion, has been studied in several vibrational levels of the first excited singlet electronic state S 1 ( 1 A u ) of glyoxal. Light complexes as H2 -glyoxal display a nice state to state dissociation. Whereas the analysis of the fluorescence spectrum, together with lifetime measurements, have shown that VP is in competition with other intramolecular vibrational energy redistribution processes in these systems, as well as inter-system crossing (ISC). Glyoxal-Ar and glyoxal-Kr behave very similarly. In particular, two isomers exist with different dissociation schemes (but similar for the same isomer of Ar or Kr-complex), and Kr does not seem to enhance ISC. Thus selectivity in the dissociation routes has to be understood as a competition between these deactivation channels.